Economic impacts of a premature nuclear phase-out in Switzerland - Christoph Böhringer; Marcel Wickart; Andre Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper investigates the economic impacts of two policy proposals: "Strom ohne Atom" (SOA) and "Moratorium Plus" (MOP), both of which contain a premature phase-out of nuclear power in Switzerland. While MOP restricts business-as-usual operation time of existing nuclear power plants to 40 years, which results in a cutback of 10-20 years, SOA foresees a reduction in operation time of 20-30 years and administers combined heat and power to substitute for nuclear energy. Based on simulations with an intertemporal multi-sector general equilibrium model of the Swiss economy, we quantify the price tags for risk reduction from nuclear power operation given additional constraints on back-up technologies. Costs of accelerating the phase-out of nuclear power for an average household amount to 200 CHF/a over the next 45 years under SOA and drop to 60 CHF/a in the case of MOP. If Switzerland were to assure carbon neutrality of a premature phase-out by the use of carbon taxes, adjustment costs would increase to 230 CHF under SOA and 110 CHF under MOP.
Keywords: Q48; C68; 330; nuclear phase-out; computable general equilibrium; Kernenergiepolitik; Wirtschaftspolitische Wirkungsanalyse; Makroökonomischer Einfluss; Allgemeines Gleichgewicht; Schweiz